'I May Sound Adversarial but I am being Polite': (Im)politeness Strategies and Tactics of Self-Presentation in Electoral Concession Speeches - Hammond, Christiana (International Journal of English Language & Communication Studies, 2021)
A concession speech is considered the closure and final swan song of every campaign. As a of democratic dispensations, a defeated candidate in an election is expected to convert combative imageries of defeat into linguistic patterns and periphrasis to an audience as a sign of acceptance of defeat and rally support for the winner in the contest. Such speeches could be skilfully woven to either 'save' or 'threaten' the face of both the speaker and the target audience. Literature suggests a series of 'self-presentation' and impression management strategies are negotiated and enacted through the rhetoric of a concession speech in significantly different ways in varied contexts. This paper presents a corpus-assisted analysis of the post-election concession speech of John Dramani Mahama (JDM) of the National Democratic Congress (NDC) after the 2016 Presidential elections in Ghana. It explores (im)politeness strategies of the speech through the lens of Brown and Levinson's politeness theory, and further examines the tactics of self-presentation' through Leary's strategies of 'self-presentation and impression management. The data are descriptively analysed and thematically presented to reveal how linguistic elements could be used to signal instances of positive, negative, off-record, and bald-on-record (im)politeness. The findings showed that JDM in salvaging his political persona may have sounded adversarial but was excessively polite. The findings also indicate that JDM through the speech negotiated and enacted a series of self-presentation and impression management tactics such as self-descriptions, social associations, and attitude statements among others. The study contributes to literature on (im)politeness and impression management by concluding on the assumption that words could be manipulated politely or impolitely to illuminate a self-creation of an 'ideal identity' or 'front stage persona' as well as a 'real identity or 'back stage persona'. The paper recommends a re-definition of the space and context for a formal concession speech in an era of post-election social media rantings from defeated candidates.
Academic Journal
Keywords: SELF-presentation; MAHAMA; John Dramani; 1958-; MASS media; POLITICAL communication; VOTER intimidation; NATIONAL Democratic Congress (Ghana)